Функціювання повних і коротких форм інфінітива в поезії Миколи Бажана - Денисюк, Василь Вiкторович (SlavVaria, 2023)
Functioning of full and short forms of the infinitive in the poetry by Mykola Bazhan. The article analyzes the poems of the Ukrainian poet of the 20th c. Mykola Bazhan in the aspect of the functioning of infinitive forms. It was concluded that the artist prefers full forms of the infinitive, which, like short ones, in contexts realize one or another stylistic function, but, unlike short ones, they can also be neutral textual units. The short form implements the author’s imperative, it is a sign of expression, clarity, categoricalness, imperativeness. A significant number of uses of the short form is determined by rhyme.